Nickel hyperaccumulation is independent of the leaf economics spectrum, although it may be linked to plant water balance in an ultramafic plant community from Sabah (Malaysia) - Celestino Quintela-Sabarís; Michel-Pierre Faucon; Béatrice Gervais-Bergeron; Sukaibin Sumail; Antony van der Ent; Rimi Repin; John Sugau; Reuben Nilus; Thomas Rigaudier; Guillaume Echevarria; Sophie Leguédois (Plant and Soil, 2025)
Background and aims Nickel (Ni) hyperaccumulators are a group of plants able to store elevated amounts of this element in their leaves. Some studies indicate that hyperaccumulation may be associated with traits favouring fast resource capture or with traits favouring nutrient and water conservation, but there is no evidence for the role of nickel hyperaccumulation in the leaf economics spectrum. Our study aims to assess the differences in the leaf economics spectrum between Ni hyperaccumulators and non-hyperaccumulators. Methods We have conducted a field study involving five hyperaccumulators and ten non-hyperaccumulators growing on the same ultramafic community in Sabah (Malaysia). We measured two structural and seven chemical leaf traits and computed a Principal Component Analysis, which was complemented by a test of the phylogenetic signal of each trait and linear mixed models to assess the influence of each leaf trait on nickel accumulation. Results Our analyses inferred three principal components that reflected the main environmental constraints that shape the resource acquisition strategies of the studied ultramafic plant community: leaf economics spectrum, hyperaccumulation and water-use efficiency, and calcium to magnesium balance. Moreover, the linear mixed models indicated that carbon isotope discrimination and potassium concentrations had a significant effect on Ni accumulation, suggesting that nickel might replace partially potassium in its role in plant water balance. Conclusion Overall, the data suggest that in the community studied, Ni hyperaccumulation is independent of the leaf economics spectrum and related to plant water economy. More studies with other hyperaccumulator plants are needed to confirm these findings.